2014
DOI: 10.1063/1.4866012
|View full text |Cite
|
Sign up to set email alerts
|

Decay of the supersonic turbulent wakes from micro-ramps

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. The wakes resulting from micro-ramps immersed in a supersonic turbulent boundary layer at Ma=2.0 are investigated by means of particle image velocimetry (PIV). Two micro-ramps are investigated with height of 60% and 80% of the undisturbed boundary layer, respectively. The measurement domain is Permanent repository link

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 27 publications
1
17
1
Order By: Relevance
“…The co-existence of the streamwise vortices and K-H vortices triggers the vortex interaction. Cross-correlation of their intensities revealed that the generation of K-H vortex decreases the strength of streamwise vortices [23]. It is well known that the streamwise vortices execute the flow control function, the reduced streamwise vortex intensity due to vortex interaction, in the transient sense, may affect the control result.…”
Section: Instantaneous Flow Organizationmentioning
confidence: 94%
See 2 more Smart Citations
“…The co-existence of the streamwise vortices and K-H vortices triggers the vortex interaction. Cross-correlation of their intensities revealed that the generation of K-H vortex decreases the strength of streamwise vortices [23]. It is well known that the streamwise vortices execute the flow control function, the reduced streamwise vortex intensity due to vortex interaction, in the transient sense, may affect the control result.…”
Section: Instantaneous Flow Organizationmentioning
confidence: 94%
“…The decay of wake velocity profile was also studied by Herges et al [22] using Stereo-PIV. Sun et al [23] paid special attention on the decay behavior till downstream position of x/h=30 in the center plane using planar PIV and formulated an exponential decay law for both the maximum deficit velocity (Umin) and peak upwash velocity (Vmax). The recovery of deficit velocity as well as the elevation of the deficit region are visualized in figure 11, whereas the decay of upwash velocity in center plane can be seen in figure 12.…”
Section: The Velocity Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of the micro-ramp wake have dealt with the streamwise evolution of the momentum deficit and characterized its turbulent recovery (Ghosh, Choi & Edwards 2010;Sun et al 2014b). In the present case, the momentum deficit and the properties of the shear layer induced by the micro-ramp pertain to the laminar regime and the velocity profile in the symmetry plane (z/h = 0) is compared with that of the undisturbed boundary layer.…”
Section: Momentum Deficit and Log-layermentioning
confidence: 99%
“…The instantaneous flow organization shows the presence of a train of arc-shaped vortices at the edge of the wake due to the K-H instability. In the downstream wake region of the micro-ramp, the K-H instability at the upper shear layer further develops with the onset of vortex pairing (Sun et al 2014b). In a more recent numerical study, Sun et al (2014a) also investigated the temporal evolution of the latter vortices, concluding that the onset of arc-like vortices pairing and connection at the bottom in the downstream region contributes to the distortion of the streamwise counter-rotating vortex pair.…”
Section: Introductionmentioning
confidence: 98%